Poetic Devices in the English-Language Lyrics of Fourth Generation K-pop Girl Groups - Kujanpää, Juuso (My University, 2026)
This study examines the poetic devices used in the English-language lyrics of fourth generation K-pop girl groups. The aim of the study was to observe the English-language usage in K-pop and observe whether there are underlying reasons for its use. The research focused on twelve singles from three groups, namely aespa, IVE and LE SSERAFIM, with only the English-language lyrics being analyzed. The research used a manual coding system where all cases of hyperboles, metaphors and similes were identified from the data. Metaphors were the most observed, followed by hyperboles and finally similes. Metaphors often were used to display identity and value of the artists. The findings suggest that English is used as a marketing tool but also as a meaning-making tool that allows the artists to construct their identities. Limitations of the study focused on the small sample size and the reliability of the coding process. Future research should expand the sample size and look into the listener’s point of view as well explore the possibility of a cross-genre analysis.
Keywords: K-pop; English in popular music; stylistics; hyperbole; metaphor; simile; identity construction